Rapid and sensitive detection of Citrus Bacterial Canker by loop-mediated isothermal amplification combined with simple visual evaluation methods - Rigano, Luciano Ariel (2010)
Citrus Bacterial Canker (CBC) is a major, highly contagious disease of citrus plants present in many countries in Asia, Africa and America, but not in the Mediterranean area. There are three types of Citrus Bacterial Canker, named A, B, and C that have different genotypes and posses variation in host range within citrus species. The causative agent for type A CBC is Xanthomonas citri subsp. citri, while Xanthomonas fuscans subsp. aurantifolii, strain B causes type B CBC and Xanthomonas fuscans subsp. aurantifolii strain C causes CBC type C. The early and accurate identification of those bacteria is essential for the protection of the citrus industry. Detection methods based on bacterial isolation, antibodies or polymerase chain reaction (PCR) have been developed previously; however, these approaches may be time consuming, laborious and, in the case of PCR, it requires expensive laboratory equipment. Loop-mediated isothermal amplification (LAMP), which is a novel isothermal DNA amplification technique, is sensitive, specific, fast and requires no specialized laboratory equipment.